Combating money laundering in the conditions of economic instability - D. S. Ananikyan (Путеводитель предпринимателя, 2020)
The growing relevance of counteraction to legalization (laundering) income in conditions of economic instability (crisis and sanctions)related to political instability and problems of increase of efficiency of activity of the Russian specialized structures (Rosfinmonitoring, law enforcement), the conclusion is that legalization has become one of the global threats to economic security, which requires coordination and harmonization of interventions.